1998
DOI: 10.1111/j.1469-7793.1998.867bj.x
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids decrease excitatory synaptic transmission and impair long‐term depression in rat cerebellar Purkinje cells

Abstract: CB‐1 cannabinoid receptors are strongly expressed in the molecular layer of the cerebellar cortex. We have analysed, in patch‐clamped Purkinje cells (PCs) in rat cerebellar slices, the effect of the selective CB‐1 agonists WIN55,212‐2 and CP55,940 and of the selective CB‐1 antagonist SR141716‐A on excitatory synaptic transmission and synaptic plasticity. Bath application of both agonists markedly depressed parallel fibre (PF) EPSCs. This effect was reversed by SR141716‐A. In contrast, responses of PCs to ionop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
40
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(45 citation statements)
references
References 40 publications
(52 reference statements)
5
40
0
Order By: Relevance
“…Learning-related pauses in Purkinje cell firing have been reported in studies examining extracellular activity during dEBC (Hesslow and Ivarsson 1994;Green and Steinmetz 2005;Jirenhed et al 2007;Jirenhed and Hesslow 2011). Moreover, CB1R knockout mice and mice injected with SR14716A do not exhibit LTD (Safo and Regehr 2005), and manipulations of CB1R function, using either WIN55,212-2 or SR141716A, have been shown to impair induction of parallel fiber-Purkinje cell LTD in vitro (Lévénés et al 1998;Safo and Regehr 2005) and impair acquisition of dEBC (Steinmetz and Freeman 2010). In the current study, WIN55,212-2 was shown to slightly impair performance of conditioned responses after learning.…”
Section: Discussionmentioning
confidence: 88%
“…Learning-related pauses in Purkinje cell firing have been reported in studies examining extracellular activity during dEBC (Hesslow and Ivarsson 1994;Green and Steinmetz 2005;Jirenhed et al 2007;Jirenhed and Hesslow 2011). Moreover, CB1R knockout mice and mice injected with SR14716A do not exhibit LTD (Safo and Regehr 2005), and manipulations of CB1R function, using either WIN55,212-2 or SR141716A, have been shown to impair induction of parallel fiber-Purkinje cell LTD in vitro (Lévénés et al 1998;Safo and Regehr 2005) and impair acquisition of dEBC (Steinmetz and Freeman 2010). In the current study, WIN55,212-2 was shown to slightly impair performance of conditioned responses after learning.…”
Section: Discussionmentioning
confidence: 88%
“…Purkinje cells release 2-AG following mGluR1 activation, which binds to CB1Rs on granule cell axon terminals (Breivogel et al 2004;Kawamura et al 2006) and to GABAergic stellate and basket cell terminals (Diana et al 2002), resulting in what has been termed depolarization-induced suppression of excitation (Kreitzer and Regehr 2001a) and depolarization-induced suppression of inhibition (Kreitzer and Regehr 2001b), respectively. WIN55,212-2 and SR141716A impair induction of parallel fiber-Purkinje cell LTD in vitro (Lévénés et al 1998;Safo and Regehr 2005). LTD at parallel fiber-Purkinje cell synapses is hypothesized to produce pauses in Purkinje cell spiking that release neurons in the interpositus nucleus from inhibition (Ito and Kano 1982;Batini and Billard 1985).…”
Section: Discussionmentioning
confidence: 99%
“…AZD9272 caused a partial but dose-dependent increase in (2)-D 9 -THC-appropriate responding, with a maximal effect of 37.39%, and then a decrease with no dosedependent effects on response rates. It has been shown that activation of cannabinoid CB1 receptors reduces glutamate release in rat cerebellar purkinje cells (Lévénés et al, 1998) and in the mouse forebrain (Domenici et al, 2006), suggesting that the discriminative effects of (2)-D 9 -THC, or the components thereof, may be mediated at least partly by reducing glutamate release via the CB1 receptor.…”
Section: Discussionmentioning
confidence: 99%